Thermal stability of nanostructured iron– chromium alloys for interconnect application of solid oxide fuel cells - Khaerudini, D. S.; Sebayang, D.; Mahzan, S.; Untoro, P. (Maney on behalf of the Institute, 2012)
The thermal expansion mismatch between a metallic substrate and its external oxide scale generates a strain on cooling that is the primary cause of spallation of protective oxide scales. This study investigates the thermal stability, by means of thermal expansion and oxidation behaviour, of the nanostructured FeCr alloy prepared by different consolidation techniques by means of the spark plasma sintering (SPS) method and to compare with conventional sintering technique by means of hot pressing (HP). This has potential application as interconnect in solid oxide fuel cell. Commercially available ferritic steel is chosen as a comparison of another high Cr ferritic model alloy. The beneficial effect of the reactive element by means of lanthanum onto the alloy surface that is introduced using ion implantation is also explored. The specific aspects studied were the effects of nanocrystalline structure, influenced by sintering method and surface treatment through La ion implantation of chromia forming alloys, which may improve their high thermal stability. Oxidation testing was conducted at 900–1100uC for 100 h in laboratory air. Characterisations using X-ray diffraction, scanning electron microscopy and energy dispersive Xray spectroscopy were carried out before and after each route or process to investigate the microstructure, phase change and formation of the oxide layer. The results revealed that the FeCr alloy prepared by SPS were more effective to retain nanocrystalline and better properties than those prepared by HP and the commercially available ferritic alloy. For all types of specimens, the presence of La had no detectable effect on thermal expansion but a major effect on scale adherence. The coefficients of thermal expansion for the alloy prepared by SPS were lower than those prepared by HP, and the scale adherence to the La implanted alloy was generally superior. The results consistently showed that a better reduction in oxidation resistance corresponds to excellent nanostructured alloy and La implantation.